MANIFESTASI KLINIS DAN TATALAKSANA OPERATIF DEGENERASI KORNEA NODULAR SALZMANN - Nisa, Viendri Firhand; Mustaram, Arief Akhdestira (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2023)
Introduction: Salzmann nodular degeneration (SND) is an idiopathic and degenerative noninflammatory condition of the cornea. SND is characterized by a grayish-white or blue-white subepithelial nodule. Mild symptoms may improve with lubrication and topical anti-inflammatory therapy. Visual disturbances may occur and surgery may be required. Purpose: To explain clinical manifestations and operative management of corneal Salzmann nodular degeneration. Case Report: A 63-year-old woman came with the chief complaint of a nodule in her left eye since 4 months ago. Complaints accompanied by blurry vision, watery eyes and glare. Ophthalmological examination revealed a regression of visual, a nodule in the corneal stroma was grayish white. After examination, the patient was diagnosed with Salzmann OS nodular degeneration and ODS immature senile cataract. Debridement keratectomy and amniotic membrane transplantation (AMT) were performed as the management of this patient. Anatomical pathology results clinically support Salzmann's nodular degeneration. Discussion: Slow-progressive, yellowish-white nodules are characteristic of SND. SND can be asymptomatic, mild symptoms, or until there is a decrease in visual function. It depends on the location and depth of the nodule. Several treatment options can be done ranging from conservative with topical drugs to surgery. Surgical treatment options have the goal of reducing the worsening symptoms of nodule recurrence. Conclusions: A complete history, comprehensive ophthalmological examination can help establish the diagnosis of SND. The appearance of nodules causes complaints of foreign body sensation, decreased visual function and other accompanying symptoms. Treatment needs to be given according to the patient's condition and indications, especially the selection of surgical therapy.